CURRENT TRENDS IN INNOVATIVE DEVELOPMENT OF THE CONSTRUCTION INDUSTRY IN UKRAINE: INTERNATIONAL PRACTICE (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. In the current context of globalization and integration of the Ukrainian economy into the global space, the innovative development of the construction industry is of particular importance. The development of innovative solutions in construction is becoming a critical factor in increasing the competitiveness of the industry and analyzing advanced innovative technologies used in international practice and the possibilities of their adaptation to Ukrainian realities. The purpose of the article. The purpose of the article is to search for modern trends used in international practice related to the innovative development of the construction industry in Ukraine.Methods. The study of modern trends in the innovative development of the construction industry of Ukraine involves the use of scientific research methods that provide a systematic approach to analyzing the experience of developed countries, which allows obtaining objective results that contribute to the formation of recommendations for the implementation of innovations in Ukraine.Results. The article substantiates that the construction industry of Ukraine is one of the key sectors for economic development and, in the context of globalization and constant economic changes, it needs to be adapted to new realities. It is proved that one of the main factors of sustainable development of the construction industry is the introduction of modern innovations.The successful experience of developed countries in the field of construction is considered, which demonstrates that an innovative approach to the construction process is important for increasing competitiveness, developing infrastructure and improving environmental performance. Such successful experience is determined by the use of innovative technologies, sustainable construction practices, efficient resource management and attraction of international investments. The article provides several examples of successful experience in the field of construction in different countries. Leaders in the development of sustainable construction and energy-efficient technologies, in the use of renewable energy sources for construction, in the application of advanced technologies for the construction of earthquake-resistant buildings, in the creation of a sustainable urban environment through the use of vertical construction and in the integration of various engineering systems in cities are identified.The article determines that for Ukraine, which is undergoing an intensive economic transformation, the issue of introducing international innovations is extremely relevant. The factors that confirm the importance of introducing international innovations into the construction industry of Ukraine are identified. It is substantiated that they are due to the current situation in the country, its economic and social transformations, as well as the challenges facing the national construction sector.Conclusions are drawn that require a focus on the use of energy efficient technologies, smart buildings, sustainable materials, and the integration of digital technologies, which will significantly increase the efficiency of construction processes, reduce costs, and help preserve natural resources. Leveraging international experience in construction will also help Ukraine not only modernize its sector but also become competitive in the global construction services and investment market.Conclusiоns. The unstable economic situation, the consequences of military actions and global environmental challenges create a unique environment in which innovations become not only desirable but necessary, especially in the construction industry.
Keywords: construction industry, innovative development of the construction industry, experience of developed countries in the construction industry, international practice in the construction industry.